Impactos das mudanças climáticas na demanda de água para irrigação do meloeiro (Cucumis melo L.) utilizando modelo regionalizado integrado a um sistema de informações geográficas - Oliveira, Karisia Mara Lima de (2012)
Melon is one of the most economically important crops and increasing exports in the Brazilian Northeast region. Since most of the Brazilian melon is grown in the semiarid region and depends entirely on irrigation, it is likely that climate changes underway will have significant impacts on the crop water demand and on water resources of the main producing regions. The present study aimed at analyzing the possible impacts of climate change on water requirement of the melon crop, considering two climate change scenarios, applied on a local scale. The study covered the main producing region of melon in Brazil, formed by subregions Mossoró and Açu, in state of Rio Grande do Norte state and Lower Jaguaribe in the state of Ceará. It was used the system PRECIS (Providing Regional Climates for Impact Studies), with the regional climate model HadRM3P of the Hadley Centre. In applying the model we used a data set consisting of a baseline (basic climatology) for the period 1961 to 1990 and projections of future climate, for the year 2040, for the climate change scenarios A2 and B2. To interpolate the climatic variables for the geographic coordinates of the study area it was used a geographic information system (GIS) ARCGIS 9.3®. Bearing in mind the crop season in the region, three crop cycles were considered (July to September, September to November, November to January). Reference evapotranspiration was estimated by FAO Penman-Monteith method with minimal data. Projections of climate change were mapped and showed elevations of average reference evapotranspiration of 6.2% and 7.6%, and reductions in rainfall of 38.3% and 55.9%, in the scenarios A2 and B2, respectively, at regional level. It was estimated a rise in average gross water requirement of 8.7% and 10.5% for the year 2040, in the scenarios A2 and B2, respectively.